European board and college of obstetrics and gynaecology position statement to mark "World Patient safety day – Safe maternal and newborn care" on 17th September 2021. (November 2021) - Mukhopadhyay, Sambit; Tarlatzis, Basil; Mahmood, Tahir
Abstract: Maternal morbidity and mortality remain stubborn highly in many parts of the world. Similarly Neonatal morbidity, mortality and five years survival in most of the under-resourced countries has not declined significantly over the past decades. Furthermore sexual reproductive health services provision has not met the needs of the women and there remains a huge unmet need for reliable contraception globally. This is the time for a global action plan and for all agencies to work together to achieve meaningful outcomes to improve health of women and their babies. Covid 19 pandemic has led to increase in gender based violence as well which is deplorable. European Board and College of Obstetrics and Gynaecology welcome this initiative and commits to work with all the stakeholders to improve safety and quality of care for women and the newborn.